2020
DOI: 10.2471/blt.20.265603
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of early COVID-19 cases, United Kingdom of Great Britain and Northern Ireland

Abstract: This paper was submitted to the Bulletin of the World Health Organization and was posted to the COVID-19 open site, according to the protocol for public health emergencies for international concern as described in Vasee Moorthy et al.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…In the first 3 months of the COVID-19 pandemic in the United Kingdom (UK) (late January to early April 2020), we received 754 URT samples from 425 symptomatic cases that tested positive for SARS-CoV-2 by RT-PCR targeting the RNA-dependent RNA polymerase (RdRp) gene [1] and that had a clear record of the dates of symptom onset and sample collection. These samples were collected as part of the First Few 100 surveillance study described in Boddington et al [2]. Using RT-PCR cycle threshold (Ct) values as a semiquantitative measure of SARS-CoV-2 viral load identified that the level of SARS-CoV-2 RNA in the URT was greatest around symptom onset, steadily decreased during the first 10 days after illness onset and then plateaued ( Figure 1).…”
Section: Kinetics Of Viral Rna Detection From the Respiratory Tractmentioning
confidence: 99%
“…In the first 3 months of the COVID-19 pandemic in the United Kingdom (UK) (late January to early April 2020), we received 754 URT samples from 425 symptomatic cases that tested positive for SARS-CoV-2 by RT-PCR targeting the RNA-dependent RNA polymerase (RdRp) gene [1] and that had a clear record of the dates of symptom onset and sample collection. These samples were collected as part of the First Few 100 surveillance study described in Boddington et al [2]. Using RT-PCR cycle threshold (Ct) values as a semiquantitative measure of SARS-CoV-2 viral load identified that the level of SARS-CoV-2 RNA in the URT was greatest around symptom onset, steadily decreased during the first 10 days after illness onset and then plateaued ( Figure 1).…”
Section: Kinetics Of Viral Rna Detection From the Respiratory Tractmentioning
confidence: 99%
“…Case definitions for SARS-CoV-2 testing varied over the course of the first peak of the pandemic (table 1). 9 Throughout this period, confirmed cases and their close contacts were isolated to prevent transmission into the community. During the delayed phase of outbreak control, emphasis was shifted to testing those presenting to hospital with suspected COVID-19 with the aim of rapidly diagnosing cases and protecting those who were SARS-CoV-2 negative.…”
Section: Methodsmentioning
confidence: 99%
“…These include BNF codes from OpenPrescribing.net, published codelists for asthma, [24][25][26] immunosuppression, [27][28][29] psoriasis, 30 SLE, 31 RA 32,33 and cancer, 34,35 and Read Code 2 lists designed specifically to describe groups at increased risk of influenza infection. 36 Read Code 2 lists were added to with SNOMED codes and cross-checked against NHS QOF registers, then translated into CTV3 with manual curation. Decisions on every code list were documented and final lists reviewed by at least two authors.…”
Section: Covariatesmentioning
confidence: 99%